Digital platform tactics: How to implement platform strategy over time - Matthias Trischler; Philip Meier; Daniel Trabucchi (Journal of Business Models (JOBM), 2021)
Platform-based business models are increasingly relevant. Scholars mainly focus on the strategic dimension, but what are the tactics to build and evolve digital platforms? This article proposes a novel framework, which assists in subdividing the scope of possible activities of digital platform sponsors in a temporal and contextual manner. The framework comprises four context dimensions (platform attributes, core product, governance, ecosystem) and four lifecycle phases (birth, expansion, leadership, renewal). In particular, three key insights emerge regarding the critical role of the leadership phase (in terms of institutional and regulatory influence and the need to build a defense) as well as a lack of studies in the renewal phase.
Keywords: 650